The effects of Al substitution and partial dissolution on ultrathin NiFeAl trinary layered double hydroxide nanosheets for oxygen evolution reaction in alkaline solution. (May 2017) - Liu, Haixia; Wang, Yanrong; Lu, Xinyao; Hu, Yi; Zhu, Guoyin; Chen, Renpeng; Ma, Lianbo; Zhu, Hongfei; Tie, Zuoxiu; Liu, Jie; Jin, Zhong
Abstract: Recently, Ni–based layered double hydroxide (LDH) materials have attracted growing interest owing to the remarkable performance for oxygen evolution reaction (OER). Here we demonstrate the preparation of ultrathin Ni3 FeAlx trinary LDH nanosheets with higher activity and stability than NiFe–LDH nanosheets for OER. The enhancement was derived from Al substitution, which increased the concentration of Ni 3+ active sites on the catalyst surface. Besides, low-coordinated Ni and Fe atoms and defects were formed by partial etching/dissolution of Al 3+ in alkaline solution, which further increased the activity towards OER. To improve the conductivity, Ni3 FeAlx –LDH (x=0, 0.91, 1.27 or 2.73) nanosheets were also in - situ grown on three-dimensional-networked nickel foam. The binder-free Ni3 FeAlx –LDH/Ni foam electrodes exhibited further improved catalytic performance compared to the electrodes made of powdery Ni3 FeAlx –LDHs and nafion binder. The best OER performance was presented by Ni3 FeAl0.91 –LDH/Ni foam, showing a Tafel slope of 57 mV/dec, a low overpotential (304 mV) at the current density of 20 mA/cm 2, and a current density of 235 mA/cm 2 at 1.60 V ( vs. RHE). Furthermore, the Ni3 FeAl0.91 –LDHs/Ni foam electrode showed excellent long-term stability, maintaining a stable overpotential of 320 mV at 20 mA/cm 2 after testing for 18 h. Graphical abstract: Highlights: Al-doping ultrathin Ni3 FeAlx –LDH are fabricated by hydrothermal method. The electrochemical OER performance of Ni3 FeAlx –LDH is investigated. The Ni3 FeAlx –LDH exhibits remarkable electrocatalytic activity. Possible mechanism for the OER of Ni3 FeAlx –LDH is proposed.